Recommending Web Service Based on Ontologies for Digital Repositories - Salles, Anderson; Willrich, Roberto (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2015: Proceedings of the 21st Brazilian Symposium on Multimedia and the Web, 2015)
Digital Repositories (DRs) offer functionalities for managing, storing and accessing digital contents. DRs may make available a wide range of content types, including theses, dissertations, papers, videos, works of art and literacy works. Some DRs have used recommendation systems to offer users suggestions about digital contents that they might be interested. In this paper, we propose a multi-domain Recommender Web Service supporting multiple types of recommendation audience. The flexibility of domain and audience is provided by the use of ontologies to represent domainspecific knowledge. In order to test the feasibility of our proposal, the paper presents two use cases of our Recommending Web Service.